Comparison of subcutaneous connective tissue responses among three different formulations of gutta-percha used in thermatic techniques. - Leonardo, M. R.; Utrilla, L. S.; Rothier, A.; Leonardo, R. T.; Consolaro, A. (My University, 1990)
A study of the subcutaneous connective tissue response of 24 white rats to three different formulations of gutta-percha was undertaken. The prepared specimens were examined under the light microscope after intervals of 7, 21, 60 and 120 days. The results showed identical tissue responses after the initial period of 7 days. However, after 120 days the gutta-percha supplied with the Ultrafil system presented mature granulation tissue with neither oedema nor vascular congestion, in contrast to the responses observed with the McSpadden and Obtura formulations.
Keywords: biomaterial; gutta percha; animal; chemistry; comparative study; connective tissue; drug effect; iatrogenic disease; inflammation; rat; Animal; Biocompatible Materials; Comparative Study; Connective Tissue; Gutta-Percha; Inflammation; Rats